Managing Safe And Inclusive Workplaces: Gender And Caste Diversity And The Role Of Internal Committees In Promoting Diversity And Inclusion - Dr.Jasmine Joshi (Revista Electronica de Veterinaria, 2024)
Creating safe and inclusive workplaces that promote diversity is essential for organizations to achieve success and growth. Companies that embrace diversity and inclusion can harness the power of different perspectives, ideas and experiences to drive innovation and competitiveness. However, discrimination and harassment based on gender and caste continue to be prevalent in many workplaces, resulting in a hostile and unsafe environment for employees.This research paper focuses on the role of internal committees in managing safe and inclusive workplaces, with a specific focus on gender and caste diversity. The paper explores the legal framework around diversity and inclusion in the workplace, including the Sexual Harassment of Women at Workplace (Prevention, Prohibition and Redressal) Act, 2013 (POSH). The paper examines the responsibilities of internal committees in managing workplace diversity and promoting an inclusive work culture, including addressing complaints of discrimination and harassment.The paper draws on existing literature and case studies to provide insights into the best practices for creating safe and inclusive workplaces. The research findings suggest that effective management of diversity and inclusion requires a combination of policies, procedures, training, and awareness-building initiatives. The paper concludes by highlighting the importance of internal committees in promoting diversity and inclusion in the workplace and providing a safe and supportive environment for all employees.